2017
DOI: 10.24198/pjd.vol29no1.11614
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic profile of oral squamous cell carcinoma in Yogyakarta, Indonesia

Abstract: Introduction: Oral cancer is a major health problem in the world, indicated by a high incidence of recurrence. In Southeast Asia, oral cancer ranks sixth from all cancers on the human body. The incidence of oral cancer, especially squamous cell carcinoma types, increases every year, but the prognosis and patients life expectancy are still unsatisfying enough and the reports about the profile of oral cancer is still limited.The objective of this research was to get the epidemiological profile of oral squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Epidemiological study of a disease provides key information that can be used for understanding the etiology of the disease and to plan preventive and management strategies (Gracia et al, ). This study provides descriptive epidemiology of OSCC and its characteristics in a referral cancer hospital in Nepal from 1999 to 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological study of a disease provides key information that can be used for understanding the etiology of the disease and to plan preventive and management strategies (Gracia et al, ). This study provides descriptive epidemiology of OSCC and its characteristics in a referral cancer hospital in Nepal from 1999 to 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of OSCC among Asian countries (13)(14)(15)(16) has demonstrated the value of profiling Indonesian OSCC epidemiology to give a new perspective on this disease and contribute to better prognosis and therapy planning. Previous studies in Indonesia (17)(18)(19)(20) did not report a long study period and did not highlight the role of examining histopathological features. These studies did not assess contributing factors related to advanced-stage cancer and invasion of surgical margins in resected cases.…”
Section: Clinicopathological Characteristics Predicting Advanced Stag...mentioning
confidence: 99%
“…1 Oral cancer or oral squamous cell carcinoma (OSCC) is the sixth malignant disease in the world. [2][3][4] found on the lips and buccal mucosa, gingiva, hard palate, tongue and floor of the mouth. 4 From 2007-2016, the United States reported an increased incidence of oral and pharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Gracia reported that in 2011-2015 found, 49 cases of OSCC were in the lingual area (53.8%), buccal area (20.9%), and palatal area (12.1%). 3 Oral cancer spreads rapidly and usually are diagnosed at an advanced stage with a high mortality rate. Only half of the diagnosed cases will survive more than five years, but if the cancer is detected early, about 80-90% will survive.…”
Section: Introductionmentioning
confidence: 99%